Psicoterapia da remoto. La relazione di cura in un nuovo contesto - Atzori, Emanuela (Il sogno della farfalla, 2021)
The aim of this work is to contribute to the international debate about the possibility to apply psychotherapy online obtaining the same results that one can achieve with the traditional psychotherapy defined “in presence”. With this objective, the author criticizes the use of the term “virtual” considered improper to define online psychotherapy conducted by psychotherapists, and discusses the concept of “presence” as derived in literature, in correspondence with human birth theory. Based on her clinical experience at the time of Covid-19, the author proposes that remote psychotherapy can be considered as “real and effective”, and describes the results she obtained after six months of psychotherapy using a method of intervention founded on human birth theory. The qualitative evaluation of results considered needs to be integrated with quantitative evaluations in direct and systematic replications to increase internal and external validity.